Translation and content validation of the trans-contextual model questionnaire battery and development of a web-based version for 10-to 12-year-old Danish schoolchildren - Esben Elholm Madsen; Anne-Marie Elbe; Peter Krustrup; Carsten Hvid Larsen; Malte Nejst Larsen; Mads Madsen; Tina Hansen (Cogent Education, 2021)
The trans-contextual model (TCM) offers a heuristic-based theoretical framework to understand fifth-grade Danish schoolchildren’s motivation to participate in the 11 for Health in Denmark educational football concept, as well as their intention and behaviour to participate in vigorous physical activity (PA) in a leisure-time context. The implementation of this model framework in a validated web-based version of the 3-part TCM questionnaire battery requires transparent, qualitative cross-cultural translation and adaptation so that effectiveness of the 11 for Health concept can be evaluated in a Danish context. The focus of this translation and adaptation process was on content validity and conceptual, item, semantic, and operational equivalencies. This study consisted of three parts: (1) translation and creation of a web-based questionnaire version, (2) cognitive debriefing interviews in two independent groups of schoolchildren (ten boys and six girls, Mage = 11.65 years) and (3) observation during implementation of the questionnaire battery. Through analytical triangulation of interviews and observations, we identified four themes: considerations to be taken into account in creating the web-based questionnaire battery, adjustments needed when translating the questionnaire battery, required personal information, and response categories. Further, we identified and resolved problems with regard to the introduction of the questionnaire battery, to 23 out of 57 questions, to providing personal information, and to response categories. The translated and adapted TCM questionnaire battery seems to be suitable for 10- to 12-year-old Danish schoolchildren and shows content validity. The Danish web-based version of the TCM is now ready for large-scale testing of its psychometric properties.